The Effectiveness of in-service Teacher Training Program at Faculty of Islamic Education and Teacher Training IAIN Imam Bonjol Padang - Hadeli Hadeli; Nana Sepriyanti (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
The purpose of this research is to reveal: 1. The influence of in-service Teacher Training Program (PLPG) towards the teacher competency as participant of PLPG; 2. The correlation between gender (X1) towards the teachers’ competency as participant of PLPG; .3. The correlation between Age (X2) towards the teachers’ competency as participant of PLPG; 4. The correlation between years of service towards the teachers’ competency as participant of PLPG; 5. The correlation between the number of training followed (X4) towards teachers’ competency as participant of PLPG; and 6. This research used quantitative method. The population of this research is 1.300 teachers of PLPG in 2013. By using Yamane formulation, there are 220 teachers taken as the sample. The data was analyzed by using t test and correlation analysis. The findings of the study suggested that: 1. There is a positive influence of PLPG implementation towards teachers’ competency as PLPG participant; 2. There is no significant correlation between gender (X1) and teachers’ competency as PLPG participant; 3. There is a significant correlation between Age (X2) towards teachers’ competency of PLPG; 4. There is no significant correlation between the Years of Service (X3) towards teachers’ competency as the participant of PLPG; 5. There is a significant correlation between the number of Diklat followed (X4) towards teachers’ competency as the participant of PLPG; and 6. There is a significant correlation between the effectiveness of PLPG (X5) towards teachers’ competency as the participant of PLPG. Keywords: PLPG, LPTK, teacher certificationCopyright © 2015 by Al-Ta'lim All right reserved